Evaluasi Usability Aplikasi Road Transport And Traffic Information Center (RTTIC) Kota Malang Dengan Menggunakan Metode Usability Testing - Agung Rizqi Maulana; Satrio Hadi Wijoyo; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Malang City Transportation Department in 2016 launched the RTTIC Kota Malang mobile application. RTTIC Kota Malang can help users to get the latest traffic situation information, also information about locations, telephone numbers, and important activities in Malang City. The application has been downloaded 10 thousand times by users in Google Playstore and has a rating of 2.9 from a 5 star scale. According to the users, there are several problems with the application, including screen orientation that reduces user comfort, the application's home page does not display the available menus, and the CCTV icon on Peta CCTV menu resembles another icon. Based on the problems found, usability evaluation needs to be done to assess the level of application usability. Usability testing is used as an evaluation method that includes 9 participants for application testing. The test is carried out four times, twice the task scenario test on the application and twice the task scenario test on the improvement recommendation. Two tests were conducted with the aim of comparing usability values ​​between applications with improvement recommendations. Task scenario testing on the application and improvement recommendations are done twice each to assess aspects of usability that require testing more than once. The findings of problems after conducting a post-test interview will be the basis for making improvement recommendations. Improvement recommendations are tested again like testing the application in the first time, and then the usability values ​​are compared. The increase in usability value obtained from the improvement recommendation is 10.06%.